Effects of Chinese herbal medicine on colorectal adenoma recurrence following polypectomy: a systematic review and meta-analysis - Cheng, Yi; Di, Yuan Ming; May, Brian; Zhang, Anthony Lin; Xue, Charlie Changli; Zhang, Beiping (Frontiers in Pharmacology, 2025)
ObjectivePreventing colorectal adenoma (CRA) recurrence after polypectomy is essential. However, the current evidence of Chinese herbal medicine (CHM) for CRA recurrence is still limited. This study aims to synthesize the effects of CHM as a prevention method for CRA recurrence.MethodsNine databases were searched up to May 2024. Randomised controlled trials identifying the preventive effects of CHM among people with CRA post-polypectomy were included. spreadsheets were used to collect and extract data. RevMan and STATA were used for data analysis. We performed subgroup and sensitivity analyses to explore potentially influencing variables.ResultsTwenty trials (2,325 participants) were included. The commonly used botanical drugs belonged to the categories of strengthening the spleen and anti-tumour metabolites. Compared to routine care (RC) alone, oral CHM plus RC significantly reduced the CRA recurrence rate at 12 months (RR 0.51, 95% CI [0.39, 0.67], I2 = 42%), 6 months (RR 0.44, 95% CI [0.36, 0.55], I2 = 0%), and 3 months (RR 0.46, 95% CI [0.22, 0.96], I2 = 0%) post-polypectomy. Compared to CHM placebo plus RC, San zi granule combined with RC significantly reduced CRA recurrence at 12 months post-polypectomy (RR 0.39, 95% CI [0.16, 0.93], I2 = 0%) and during the 2-year follow-up (RR 0.73, 95% CI [0.58, 0.90]). There were no significant differences between groups for treatment duration and syndromes. Additional analysis showed that oral CHM containing the botanical drugs of Si jun zi decoction plus RC reduced CRA recurrence at 12 months post-polypectomy with a low heterogeneity, compared to RC alone (RR 0.26, 95% CI [0.13, 0.54], I2 = 0%). Adverse events were similar in the above two comparisons.ConclusionOral CHM combined with RC may reduce CRA recurrence and be well-tolerated. San zi granule and Si jun zi decoction may be representative prescriptions Experimental studies of the frequent botanical drugs have found anti-cancer effects that may account for the clinical findings. Future rigorous clinical trials are needed due to low-to-moderate certainty of evidence.Systematic Review RegistrationPROSPERO (CRD42023324197), https://www.crd.york.ac.uk/PROSPERO/view/CRD42023324197.